How cannabis tourism regulation and self-regulation shape resident support for ethical cannabis tourism - Chua, Bee Lia; Au, Wai Ching Wilson; Tsang, Kee Fu Nelson; Promsivapallop, Pornpisanu; Phucharoen, Chayanon; Fakfare, Pipatpong; Lee, Jin Soo; Han, Heesup (Routledge, 2025)
Cannabis tourism is expanding amid legalization and commercialization, yet it stirs controversies over potential risks. This study explored how regulation and self-regulation affect residents’ support for ethical cannabis tourism through social cognitive theory. A survey of 560 Thai residents revealed that well-designed regulatory frameworks elevated moral obligation while mitigating moral disengagement and lowering risk perception. Conversely, moral disengagement heightened risk perceptions. Moreover, moral obligation diminished concerns about cannabis tourism’s harms. Risk perception was the most critical predictor of residents’ support. These findings highlight the need for transparent, culturally sensitive regulations to sustain social well-being while harnessing the industry’s economic benefits.